Sodium arsenite influences proliferation and apoptosis in normal thyroid cells via modulation of ER-PI3K/AKT signaling pathway - Zhihong JIANG; Hongyun LI; Xiaowei MA; Yuanyan LAI; Jun WU (环境与职业医学)
BackgroundRecent advances in understanding the toxic effects of inorganic arsenic have revealed that arsenic exposure impacts multiple endocrine organs, thereby altering their functions. However, the mechanisms underlying arsenic-induced thyroid injury remain unclear. ObjectiveTo investigate the mechanisms by which sodium arsenite (NaAsO₂) affects the proliferation and apoptosis of normal thyroid cells (Nthy-ori3-1) through the estrogen receptor (ER)-phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) signaling pathway. MethodsNthy-ori3-1 cells were cultured in vitro and divided into the following groups: a control group (complete medium without drugs, 0 μmol·L−1), and NaAsO₂-treated groups at 1, 2, and 4 μmol·L−1. Additionally, 1 μmol·L−1 of the ER inhibitor ICI182780 was used to intervene in the NaAsO₂ exposure groups, resulting in the following combinations: 1 μmol·L−1 NaAsO₂ + ICI182780, 2 μmol·L−1 NaAsO₂ + ICI182780, and 4 μmol·L−1 NaAsO₂ + ICI182780. The median lethal concentration of NaAsO₂ was determined using cell viability assay. Cell viability was assessed at 24, 36, and 48 h using Cell Counting Kit-8 (CCK-8) assay. Colony formation ability was evaluated via plate cloning assay. Apoptosis was detected using Hoechst 33342 staining. Protein and mRNA expression levels of ERα, ERβ, c-MYC, Bax, Bcl-2, PI3K, p-PI3K, AKT, and p-AKT were measured using Western blot (WB) and real-time quantitative PCR (qRT-PCR), respectively. ResultsThe median lethal concentration of NaAsO₂ was determined to be 4.034 μmol·L−1. CCK-8 assay at 24, 36, and 48 h revealed that, compared with the control group, the 1, 2, and 4 μmol·L−1 NaAsO₂ groups significantly inhibited Nthy-ori3-1 cell proliferation (P < 0.001). The plate cloning assays demonstrated a concentration-dependent reduction in colony formation ability (P < 0.001). Following the ICI182780 intervention, the cell viability and colony formation ability in the 1, 2, and 4 μmol·L−1 NaAsO₂ groups were significantly restored compared with the corresponding NaAsO₂-only groups (P < 0.001, P < 0.01). The Hoechst 33342 staining indicated that compared with the control group, the nuclear staining intensity and apoptosis levels in the 1, 2, and 4 μmol·L−1 NaAsO₂ groups increased in a concentration-dependent manner (P < 0.001). However, the ICI182780 intervention reduced the apoptosis levels in the NaAsO₂-treated groups compared with their NaAsO₂-only counterparts (P < 0.001). The WB analysis showed that, compared with the control group, the protein expression of ERα, ERβ, c-MYC, Bcl-2, p-PI3K, and p-AKT in the 1, 2, and 4 μmol·L−1 NaAsO₂ groups decreased manner (P < 0.001, P < 0.01), while the Bax expression increased in a concentration-dependent (P < 0.001); the PI3K and AKT protein levels showed no significant differences (P > 0.05). In the ICI182780-treated NaAsO₂ groups, the ERα, ERβ, c-MYC, Bcl-2, p-PI3K, and p-AKT protein expression increased (P < 0.001, P < 0.01), the Bax expression decreased (P < 0.001), and the PI3K and AKT levels remained unchanged (P > 0.05) compared with the corresponding NaAsO₂-only groups. The mRNA expression patterns of ERα, ERβ, c-MYC, Bcl-2, and Bax were consistent with the WB results. ConclusionNaAsO₂ inhibits proliferation and promotes apoptosis in Nthy-ori3-1 cells in a dose-dependent manner. The underlying mechanism likely involves NaAsO₂-mediated suppression of the ER-PI3K/AKT signaling pathway, which subsequently regulates downstream proliferation- and apoptosis-related genes.